TATAR LANGUAGE: : TENDENCIES OF CONSERVATION AND DEVELOPMENT IN POLYETHNIC SOCIETY (CASE STUDY OF RUSSIA AND KAZAKHSTAN) - S. Sultan, Dinara; G. Bochina, Tatiana; Ye. Agmanova, Atirkul; A. Zhuravleva, Yevgeniya (Gênero & Direito, 2019)
Conservation and development of minority languages in countries unique in the ethno-linguistic aspect, such as Russia and Kazakhstan, are highly relevant. Wide linguistic diversity, on the one hand, and dominance of the official Russian in Russia and the official Kazakh and Russian languages in the socio-communicative system of society in Kazakhstan, on the other hand, determine the linguistic landscape and peculiarities of multilingualism in these states. Research interest in linguistic contacts of a modern multiethnic society has determined the choice of the processes of linguistic and ethnic identification, related issues of conservation and using the native language and culture by representatives of various ethnic groups living in Russia and Kazakhstan, as well as the specifics of their interaction and mutual influence under new geopolitical conditions as the object of the study